2015
DOI: 10.1089/humc.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

A GLP-Compliant Toxicology and Biodistribution Study: Systemic Delivery of an rAAV9 Vector for the Treatment of Mucopolysaccharidosis IIIB

Abstract: No treatment is currently available for mucopolysaccharidosis (MPS) IIIB, a neuropathic lysosomal storage disease due to defect in α-N-acetylglucosaminidase (NAGLU). In preparation for a clinical trial, we performed an IND-enabling GLP-toxicology study to assess systemic rAAV9-CMV-hNAGLU gene delivery in WT C57BL/6 mice at 1 × 10(14) vg/kg and 2 × 10(14) vg/kg (n = 30/group, M:F = 1:1), and non-GLP testing in MPS IIIB mice at 2 × 10(14) vg/kg. Importantly, no adverse clinical signs or chronic toxicity were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
16
1
Order By: Relevance
“…NAGLU at 2 × 10 14 vg/kg, a dose 3.6 or 4 times larger than the two high doses in our ILI study, found 3.2 × 10 7 vg/μg genomic DNA in liver at 6 weeks post-treatment, in contrast to an average of 3.3 × 10 6 vg/μg for our study at 3 months post-treatment. 50 Thus, at least in these two comparisons (albeit with a different AAV serotype), there appears to be a 2.5- to 6-fold reduction in vector delivery to the liver, relative to dose, using ILI instead of i.v. delivery.…”
Section: Discussionmentioning
confidence: 94%
“…NAGLU at 2 × 10 14 vg/kg, a dose 3.6 or 4 times larger than the two high doses in our ILI study, found 3.2 × 10 7 vg/μg genomic DNA in liver at 6 weeks post-treatment, in contrast to an average of 3.3 × 10 6 vg/μg for our study at 3 months post-treatment. 50 Thus, at least in these two comparisons (albeit with a different AAV serotype), there appears to be a 2.5- to 6-fold reduction in vector delivery to the liver, relative to dose, using ILI instead of i.v. delivery.…”
Section: Discussionmentioning
confidence: 94%
“…However, AAV9 has a broad tissue tropism and transduces heart, skeletal muscle, and neurons in addition to liver. 47 In contrast, biodistribution studies in non-human primates show strong liver tropism of AAV3 and AAV3-ST following peripheral vein administration with minimal distribution to other organs (except for the spleen, which invariably takes up viral particles). 18 AAV5 vector has been used in a recent clinical trial for the rare inherited metabolic disorder porphyria.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study using systemic delivery of AAV9 encoding another lysosomal enzyme, a-Nacetylglucosaminidase, to treat mucopolysaccharidosis (MPS) IIIB resulted in liver toxicity associated with transgene overexpression in wild-type but not MPS IIIB mice. 65 The difference in safety outcomes across and within species raises concerns about the predictive value of preclinical dose ranging and safety studies when translating AAV gene therapies from animals to humans.…”
Section: Discussionmentioning
confidence: 99%